Navigating engineering education amidst the post-pandemic era: Enhancing engineering education through blended learning with a flipped classroom approach - Sidhu M.S.; Low M.C.; Kang L.C. (IGI Global, 2025)
This study explores the challenges and opportunities in engineering education arising from the post-pandemic landscape. In response to the evolving educational paradigm, the research focuses on the implementation of a blended learning model with a flipped classroom approach to enhance the effectiveness of engineering education. The study employs empirical methods to assess the impact of this pedagogical shift on student engagement, learning outcomes, and overall educational experience. The investigation involves the integration of traditional face-to-face instruction with online resources and interactive digital content. The research mainly evaluated the efficacy of the blended learning approach with flipped classroom approach. Preliminary findings suggest that the adoption of blended learning with a flipped classroom approach positively influences student learning outcomes, fosters a more dynamic and participatory learning environment, and addresses the challenges posed by the post-pandemic educational landscape. ? 2024 by IGI Global.